Randomised controlled trial of long-term maintenance corticosteroid therapy in patients with autoimmune pancreatitis. Issue 3 (19th August 2016) - Masamune, Atsushi; Nishimori, Isao; Kikuta, Kazuhiro; Tsuji, Ichiro; Mizuno, Nobumasa; Iiyama, Tatsuo; Kanno, Atsushi; Tachibana, Yuichi; Ito, Tetsuhide; Kamisawa, Terumi; Uchida, Kazushige; Hamano, Hideaki; et al.
Abstract : Objective: Corticosteroid has been established as the standard therapy for autoimmune pancreatitis (AIP), but the requirement for maintenance corticosteroid therapy is controversial. We conducted a randomised controlled trial to clarify the efficacy of maintenance corticosteroid therapy in patients with AIP. Design: We conducted a multicentre, tertiary setting, randomised controlled trial. After the induction of remission with the initial oral prednisolone (PSL) treatment, maintenance therapy with PSL at 5–7.5 mg/day was continued for 3 years or withdrawn at 26 weeks. The primary endpoint was relapse-free survival over 3 years and the secondary endpoint was serious corticosteroid-related complications. All analyses were performed on an intention-to-treat basis. Results: Between April 2009 and March 2012, 49 patients with AIP were randomly assigned to the maintenance therapy group (n=30) or the cessation group (n=19). Baseline characteristics were not different between the two groups. Relapses occurred within 3 years in 11 out of 19 (57.9%) patients assigned to the cessation group, and in 7 of 30 (23.3%) patients in the maintenance therapy group. The relapse rate over 3 years was significantly lower in the maintenance therapy group than that in the cessation group (p=0.011). The relapse-free survival was significantly longer in the maintenance therapy group than that in the cessation group (p=0.007). No serious corticosteroid-related complications requiring discontinuation of PSL were observed. Conclusions: Maintenance corticosteroid therapy for 3 years may decrease relapses in patients with AIP compared with those who discontinued the therapy at 26 weeks. Trial registration number: UMIN000001818; Results.